Evaluation of some quality characteristics of some malt drinks products available in local markets in Brack , Libya - Ahmed, Mohammed Abdullah; Al Jerbi, Ali Mokhtar; Abdul Salam, Aya Ali; Abdul Karim, Izdihar; Al - Zoe, Jamal Ibrahim (Arab Journal for Sciences and Research Publishing, 2016)
There are many brands of non-alcoholic malt drinks in Brack markets-Libya, available from different sources, imported from different countries. The aim of this work was to investigate whether such brands comply with the Libyan standard specifications number 368 for alcoholic malt drink issued by the national centre for specifications and standards and to what extent these specifications are applied and restricted with. This study was conducted in the Food Technology Department of the Faculty of Engineering Sciences and Technology, Sebha University. Twelve different flavoured samples of three popular commercial brands of malt drinks (Barpican, Fayrouz and Mousee) were analysed for pH, level of sugar, total soluble solids, ash, saponin. Malt drinks were found to be acidic with pH range of 3.56 - 3.84. While the Libyan standard specifications did not include the limits of pH, the results showed that all malt drinks samples were not in compliance with the Egyptian standard specifications (ESS 2005) and Gulf standard specifications (GSS 2007) with regard to pH. Barpican brand has the highest level of total sugars of 14.80%. Total soluble solids ranged from 11.00 – 14.50% and were in compliance with the standard specifications.
Keywords: quality; malt liquor; Brak city; Libya